Selective recognition of uranyl ions from bulk of thorium(iv) and lanthanide(iii) ions by tetraalkyl urea: a combined experimental and quantum chemical study. Issue 25 (31st May 2016) - Vats, Bal Govind; Das, Debasish; Sadhu, Biswajit; Kannan, S.; Pius, I. C.; Noronha, D. M.; Sundararajan, Mahesh; Kumar, Mukesh
Abstract : A selectivity for uranyl ions in the presence of interfering Th(iv ) and other lanthanide ions from a nitric acid medium was exclusively achieved using tetraalkyl urea. Abstract : The selective separation of uranyl ions from an aqueous solution is one of the most important criteria for sustainable nuclear energy production. We report herein a known, but unexplored extractant, tetraalkyl urea, which shows supreme selectivity for uranium in the presence of interfering thorium and other lanthanide ions from a nitric acid medium. The structural characterization of the uranyl complex (UO2 X2 ·2L, where X = NO3 −, Cl − and Br − ) by IR, NMR and single crystal X-ray diffraction provides insight into the strong interaction between the uranyl ion and the ligand. The origin of this supreme selectivity for uranyl ions is further supported by electronic structure calculations. Uranyl binding with the extractant is thermodynamically more favourable when compared to thorium and the selectivity is achieved through a combination of electronic and steric effects.